THE GENESIS OF THE NEWEST CHALLENGES OF THE GLOBAL LABOR MARKET (Вісник: Міжнародні відносини, 2021)
The article examines the latest challenges in the global labour market and considers their impact on international migration processes, proposes a vector for solving these challenges. The current challenges in the world labour market such as digitalization, globalization and regionalization,neoprotectionism, urbanization, climate change, population aging, the tendency to reduce working hours due to new technologies, robotics, special attention is paid to the latest problems, including quarantine restrictions, provoked by COVID-19 pandemic. The above trends lead to the fact that the most profitable investments at the moment (and probably in the future) are investments in the human capital. This article is a part of a study of theimpact of international labour migration on the new geoeconomic area formation.
Keywords: global labour market, international migration, labour migration, COVID-19.